2020
DOI: 10.1038/s41598-019-56880-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high fat diet consumption reduces liver alpha7 nicotinic cholinergic receptor expression and impairs insulin signalling in the offspring

Abstract: LpS treatment. To induce inflammatory response, mice were treated with LPS diluted in sterile saline and administered intraperitoneally (IP) once a day for three days (1 mg kg −1 bw-IP). Mice were euthanized 2 hours after LPS treatment, and fragments of liver were collected, froze in liquid nitrogen and stored at −80 °C until processing. In vitro experiments. Hepatoma cell line, Hepa-1c1c7 (ATCC ® CRL-2026 ™), derived from mice was used to evaluate the ability of the cholinergic pathway to modulate AKT phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The adverse nutritional environment in early life might be one of the important factors in deciphering the rapid development of obesity and metabolic disorders. During the last decade, growing numbers of animal experimental models have demonstrated that maternal obesity or HFD resulted in increased offspring susceptibility to metabolic disorders (Campodonico-Burnett et al, 2020;Costa et al, 2020). Concordantly, our study also demonstrated that maternal HFD not only led to glucose and lipid metabolic disturbances in dams but also programmed glucose intolerance and disorders of serum lipid profiles in male offspring from young into adulthood.…”
Section: Discussionsupporting
confidence: 81%
“…The adverse nutritional environment in early life might be one of the important factors in deciphering the rapid development of obesity and metabolic disorders. During the last decade, growing numbers of animal experimental models have demonstrated that maternal obesity or HFD resulted in increased offspring susceptibility to metabolic disorders (Campodonico-Burnett et al, 2020;Costa et al, 2020). Concordantly, our study also demonstrated that maternal HFD not only led to glucose and lipid metabolic disturbances in dams but also programmed glucose intolerance and disorders of serum lipid profiles in male offspring from young into adulthood.…”
Section: Discussionsupporting
confidence: 81%
“…There is much evidence that maternal obesity and/or high-caloric diet consumption during pregnancy and lactation can promote adverse metabolic outcomes in offspring ( Zambrano et al, 2010 ; Alfaradhi et al, 2014 ; Benatti et al, 2014 ; Melo et al, 2014 ; Gaillard, 2015 ; Fante et al, 2016 ; Simino et al, 2017 ; Costa et al, 2020 ). Among the most well-characterized alterations in the liver of the offspring of obese dams, the development of NAFLD and its interconnection with insulin resistance has been widely explored ( Watt et al, 2019 ; Tanase et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine plays a dual role in obesity as a low-grade inflammatory disease. Maternal nicotine consumption not only dysregulates energy metabolism, including hormonal imbalance (leptin, insulin), even it increases the risk of metabolic syndromes such as obesity and hyperleptinemia and larger adipocytes in the offspring during adulthood [ 236 , 237 ]. In obese patients, nicotine’s positive effect on energy metabolism, including glucose and insulin, is associated with the suppression of inflammatory signaling pathways [ 238 ].…”
Section: Nicotine In Diseasesmentioning
confidence: 99%